2015
DOI: 10.1590/0004-282x20140239
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian consensus on guidelines for diagnosis and treatment for restless legs syndrome

Abstract: The Consensus on restless legs syndrome is an effort of neurologists from several Brazilian states, which tirelessly reviewed the literature of recent years in search of evidence, both in regard to diagnosis and treatment, according to the Oxford Centre for Evidence-based Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 118 publications
(136 reference statements)
0
3
0
Order By: Relevance
“…To date, the treatment for Willis-Ekbom disease (WED) 20 , 401 , which is known as restless legs syndrome (RLS), and for periodic limb movements during sleep 402 (PLMS) is pharmacological and non-pharmacological 402 , with physiotherapeutic interventions used as an adjunctive therapy. Despite being 2 different entities, both phenomena often occur simultaneously, and the absence of WED is a criterion for the medical diagnosis of periodic limb movement disorders (PLMD).…”
Section: Willis-ekbom Disease and Periodic Limb Movement Disordermentioning
confidence: 99%
“…To date, the treatment for Willis-Ekbom disease (WED) 20 , 401 , which is known as restless legs syndrome (RLS), and for periodic limb movements during sleep 402 (PLMS) is pharmacological and non-pharmacological 402 , with physiotherapeutic interventions used as an adjunctive therapy. Despite being 2 different entities, both phenomena often occur simultaneously, and the absence of WED is a criterion for the medical diagnosis of periodic limb movement disorders (PLMD).…”
Section: Willis-ekbom Disease and Periodic Limb Movement Disordermentioning
confidence: 99%
“…Gabapentin also plays a positive role in the treatment of RLS, but drowsiness, dizziness, headache and tremors are reported as side effects. Also gabapentin has urinary excretion and long half‐life among HD patients [15]. Patients' sleep disorders can be controlled with benzodiazepines, but these drugs increase daytime sleepiness and the resulting problems, including falls, in patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…In Iran, based on the results of study by Amiri et al, the prevalence of RLS was reported as 67.2% [13]. This syndrome causes chronic insomnia and daytime sleepiness, and therefore affects the patients' quality sleep [14,15]. Patients with moderate to severe RLS may sleep less than 5 h at night [16].…”
Section: Introductionmentioning
confidence: 99%